Determination of immunogenic proteins of mumps virus by immunoblot assay - Kalkan, A.; Bulut, Y.; Bulut, H.; Doymaz, M.Z. (My University, 2000)
The aim of this study was to determine the viral proteins of mumps virus infected VERO cells by using immunoblot technique performed after sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The protein profiles of infected and non-infected cell lysates have been compared and 2 additional protein lines which have 60 and 20 kDa molecular weights were detected in infected cell samples after electrophoresis and staining with Coomassie blue, whereas there were no major-differences in protein patterns between them. In immunoblot assays performed by using high titered mumps virus specific haemagglutination inhibition antibodies and lysates of infected and control cells, 4 different protein lines which have 32, 60, 72 and 80 kDa molecular weights have been detected, supposed corresponding with matrix, fusion-1, nucleocapsid and haemagglutinin-neuraminidase proteins respectively which were the immunogenic proteins of the virus.
Kabakulak virusunun immunojenik proteinlerinin immunoblot yontemiyle gosterilmesi
Keywords: Immunoblot technique; Mumps virus; SDS-PAGE